Interface morfologia e sintaxe em Tenetehára - Ricardo Campos de Castro (2007)
This dissertation aims at making an interface amongst morphology and syntaxin the Tenetehára language. We analyze morphemes which increase and decreaseverbal valence, morphemes of absolutive and of nominative Case, oftime/aspect/mood and of negation. Starting with the occurrence of verbal affixes, itwas proposed a linear arrangement in which these affixes occur in the verbalparadigm. We still examined the morphosyntactic behavior of certain verbs whichpresent incorporated objects in order to provide additional evidence to the hypothesisof unergativity, according to which unergatives are implicit transitives, in agreementwith Hale e Keyser hypothesis (1993). The study of the causative prefix {-mu} alsoreveals that such prefix constitutes an expedient of increasing the valence of verbswith only one argument. The reflexive prefix {-ze} has the function of decreasing theverbal valence and of indicating the middle voice. We also show that the suffix {-har} derives nouns from verbs of action in a similar way to the suffix {-(d)or} ofPortuguese. Therefore, the co-occurrence of the suffix {-har} with unacusative verbswill result in an ungrammatical sentence. Such bad formation is directly related withthe fact that unacusative verbs does not select a D/NP agent, once that they aredefectives verbs for not projecting the Spec-vP position. Additionally, having in mindthe scope of occurrence of the suffix {-har}, we propose to question the stronglexicalist hypothesis which was originally proposed by Chomsky (1970, 1995),according to which all the process of word formation happens in the lexical level. Ouranalysis has revealed that the suffix {-har} can generate nouns from complexconstituents and not only from simple stems.